2021
DOI: 10.3390/ani11051265
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Impact of Bee Pollen Supplementation on Macroscopic and Microscopic Structure of Femoral Bone in Rats

Abstract: Bee pollen has been successfully used as a feed additive with beneficial impacts on productive, reproductive, and immune conditions of animals. However, its effect on bone structure and bone health remains controversial. Therefore, the purpose of our study was to examine the impact of bee pollen supplementation on macroscopic and microscopic structure of a femoral bone using rats as suitable animal models. Male rats (1 month-old) were assigned into three groups: control (C group) that was fed a standard diet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The results showed that there was no significant difference in the level of alanine aminotransferase and aspartate aminotransferase in the group of 21 birds/m 2 supplemented with 20 and 30 gm of bee pollen compared to the control group, and when 20 and 30 gm of bee pollen were added to the bird population density group, Similarly the results of Martiniakova et al [45] showed no significant difference in ALT levels when bee pollen was added and, on the contrary, lower values of AST were shown in the 0.5% and 0.75% groups of bee pollen. Perhaps the reason is that bee pollen improves liver function and reduces liver damage, and perhaps the protective effect of bee pollen on the liver is due to the antioxidant content of some flavonoids such as quercetin, which plays a role as an antioxidant against oxidants that cause liver damage [46].…”
Section: Discussionsupporting
confidence: 59%
“…The results showed that there was no significant difference in the level of alanine aminotransferase and aspartate aminotransferase in the group of 21 birds/m 2 supplemented with 20 and 30 gm of bee pollen compared to the control group, and when 20 and 30 gm of bee pollen were added to the bird population density group, Similarly the results of Martiniakova et al [45] showed no significant difference in ALT levels when bee pollen was added and, on the contrary, lower values of AST were shown in the 0.5% and 0.75% groups of bee pollen. Perhaps the reason is that bee pollen improves liver function and reduces liver damage, and perhaps the protective effect of bee pollen on the liver is due to the antioxidant content of some flavonoids such as quercetin, which plays a role as an antioxidant against oxidants that cause liver damage [46].…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, it is recommended to increase the sample size and include animals of both sexes in future studies. Additionally, conducting further experiments with different doses of bee pollen and extending the supplementation period would provide valuable insights and enhance our understanding of its effects ( Martiniakova et al, 2021 ).…”
Section: Other Honeybee-derived Productsmentioning
confidence: 99%
“…Bee workers (Apis mellifera) gather flower pollen from various plant sources to create bee pollen (Attia et al, 2014). Bee pollen generally consists of 25 to 30 % protein, 30 to 55 percent carbohydrates, 1 to 20 percent fatty acids and lipids, as well as vitamins, minerals, sterols, phenolic acids and flavonoids (Martiniakova et al, 2021). Bee pollen contains essential nutrients that have a beneficial nutritional effect on reproductive effectiveness; as mentioned by Wang et al (2002), adding 1 and 1.5 % bee pollen improved semen quality and increased broiler chicken activity and sperm concentration.…”
Section: Introductionmentioning
confidence: 99%